Analisis Faktor-Faktor Work From Home untuk Menilai Kinerja Karyawan Astra Credit Companies Bekasi Pandemi Covid-19 - Julio Immanuel (Jurnal Syntax Transformation, 2022)
The purpose of this study is to analyze the factors of working from home (Work From Home) to assess employee performance during the COVID-19 pandemic in finance companies. The research method used in this research is descriptive qualitative method. The type of data used in this research is qualitative data. In this study, 5 employees of Astra Credit Companies (ACC) were used as resource persons. The results of this study are that work from home makes employees more flexible in doing their jobs andcan provide solutions to save operational costs and limit the spread of the Covid-19 Virus through Social Distancing